Pengenalan Kosakata Bahasa Inggris menggunakan Video Animasi Pendek Berbahasa Inggris di TK Masjid Syuhada - Cahyaningrum, Tri; Setianingsih, Ika Sulis (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
The importance of English proficiency has led to greater attention being given to English instruction for young children. Young learner is recognized as an ideal period for language learning, which requires the use of appropriate media and teaching methods. This community service activity aims to support children in learning and practicing English in a fun and engaging way by using short animated videos. The activity was carried out at TK Masjid Syuhada, using the video “The Bear and the Bee” to introduce vocabulary related to emotions and parts of the body. A total of 13 students participated enthusiastically in all stages of the activity. The activity results that the kindergarten students were motivated in learning English vocabulary and simple expression using short animated video. The students’ enthusiasm during the activity show that short animate video is an interesting media and beneficial to be used in teaching English for young learner.